The effect of rosehip (Rosa canina L.) supplementation to diet on the performance, egg and meat quality, antioxidant activity in laying quail - Konca, Yusuf; Kaliber, Mahmut; Uzkulekci, Hasan Huseyin; Cimen, Behzat; Yalcin, Hasan (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study was conducted to determine the effects of rosehip (RS, Rosa canina L.) supplementation on the performance, carcass traits, meat quality, serum antioxidant activity, egg yolk pigmentation and fatty acid composition of laying quail. A total of 120 10-week-old laying quail were divided into 5 treatment groups with 8 replicates. The treatments were as follows: the first group was fed control diet (C, no rosehip addition), other groups (2, 3, 4 and 5) were fed with diets containing 2.5, 5, 10 and 15% RS, respectively. The body weight (BW), feed consumption (FC) and egg yield were not affected by the treatments. However, egg weight and egg mass increased with 5 and 10% RS supplementation (P<0.01). The breast meat’s dry matter, crude protein, ash, fat, drip loss, thawing loss, cooking loss, postmortem pH1 values and the colour were not statistically influenced by RS supplementation. Rosehip supplementation caused a decrease in the L* values of egg yolk colour, however, the redness (a*) and yellowness (b*) values of the egg yolk was higher than that of the C group (P<0.01). Rosehip supplementation did not change the fatty acid composition of egg yolk. Rosehip addition at 2.5 and 5% ratio to diets decreased serum malondialdehyde (MDA), and increased serum superoxide dismutase (SOD) levels (P<0.01); while addition of 10 and 15% RS caused an increase in serum MDA and decrease in serum SOD levels compared to C group (P<0.01). In conclusion, rosehip as a feed ingredient in quail diets can be used to increase egg weight, egg mass and egg yolk pigmentation and low (2.5 and 5%) RS supplementation may decrease serum oxidant activity but not high concentrations (10 and 15%) of RS.